The Relationship of Urban Life to Selfishness: (A Study of Urban Analysis) - Abdullah Esmail Hemed; Kameran Jewher Abdullah (QALAAI ZANIST JOURNAL, 2024)
The aim of this study is to present the impact of (economic conditions, social change, and the role of the city) in the development of selfishness. In this study, researchers seek to find a relationship between independent variables which is (urban life) and dependent variables which is (the development of selfishness). Therefore, the analytical method was used in this study. In this study, researchers reached some crucial conclusions, such as The results of this study have revealed that, in private property, economic conditions impact the development of selfishness, Because the objective of individuals in the capitalist world is to make the maximum profit and achieve personal interests, which leads to an authoritarian, utilitarian, arrogant, and selfish personality. Results have shown that social change plays a critical role in developing selfishness, which is a consequence of the formation of new values, that leads to social change within the private property system, therefore it increases the sense of oppression and self-imposition. This study also found that some cities’ characteristics such as (different professions, different directions, economic and social inequality, imitation, private property, conflict, individual thought, distrust, and apparent consumption) are contributing to to the development of selfishness.